Republicans, Martyrology, and the Death Penalty in Britain and Ireland, 1939–1990. (5th June 2015) - Doyle, David Matthew
Abstract This article examines the relationship between politically motivated murder, martyrdom, and the death penalty in Britain and Ireland in the period from 1939 to 1990. First, it investigates the nexus between historical experience and memory, political martyrdom, and capital punishment as it applied to Irish Republicans in Britain during the Second World War. Secondly, it examines the use of extraordinary legal powers to impose the death penalty in the Irish state during the "Emergency, " and charts the processes through which the threat of capital punishment continued to be perceived as an essential instrument of security in both Irish jurisdictions in the postwar period. Thirdly, it evaluates the effectiveness of the death penalty in deterring politically motivated murder and explores the anomalous, paradoxical decision to abolish capital punishment at the height of subversive killing in Northern Ireland. The essay concludes that the national security issue and the potential martyrdom of Irish Republicans were pivotal factors in dissuading successive British governments from reintroducing the death penalty for politically motivated offenses in Britain and Northern Ireland.